2016
DOI: 10.1089/neu.2014.3844
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Community Integration Trajectories in the First Five Years after Traumatic Brain Injury

Abstract: The aims of this study were to assess the trajectories of community integration in individuals with traumatic brain injury (TBI) through one, two, and five years post-injury and to examine whether those trajectories could be predicted by demographic and injury characteristics. A longitudinal cohort study was conducted with 105 individuals with moderate-to-severe TBI admitted to a trauma referral center in 2005-2007. Demographics and injury-related factors were extracted from medical records. At the one-, two- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 46 publications
5
29
1
Order By: Relevance
“…Age and gender had no impact on community reintegration. However, injury severity influenced community integration, in line with previous studies (Andelic et al., ; Sandhaug, Andelic, Langhammer, & Mygland, ; Winkler, Unsworth, & Sloan, ). The results also showed significant improvements in the community integration from 10 to 20 years both in between and within TBI severity groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Age and gender had no impact on community reintegration. However, injury severity influenced community integration, in line with previous studies (Andelic et al., ; Sandhaug, Andelic, Langhammer, & Mygland, ; Winkler, Unsworth, & Sloan, ). The results also showed significant improvements in the community integration from 10 to 20 years both in between and within TBI severity groups.…”
Section: Discussionsupporting
confidence: 87%
“…A large proportion of patients with moderate and severe traumatic brain injury (TBI) sustain long‐term physical, cognitive, and emotional impairments that have a deep impact on their functioning, reintegration to society and health‐related quality of life (HRQL; Andelic et al., ; Forslund, Roe, Sigurdardottir, & Andelic, ; Hammond et al., ; Jacobsson, Westerberg, Soderberg, & Lexell, ; Ponsford, Draper, & Schonberger, ; Schulz‐Heik et al., ; Sigurdardottir, Andelic, Roe, & Schanke, ; Wilson et al., ). TBI outcomes up to 10 years postinjury have been documented in several studies (Andelic et al., , ; Dahm & Ponsford, ; Jourdan et al., ). The findings suggest that patients with moderate and severe TBI experience persisting functional limitations and decreased employment rates (Andelic et al., ; Forslund et al., ; Ponsford et al., ), reduced physical and mental health and elevated probabilities of social isolation (Andelic et al., ; Hawthorne, Gruen, & Kaye, ).…”
Section: Introductionmentioning
confidence: 96%
“…The severity of insomnia was found to be a main factor independently associated with community integration [ 34 ], perceived disability severity [ 33 ], more severe fatigue and diminished alertness [ 36 ]. Consistent with previous research [ 39 ], we observed a trend toward better community integration in females compared with males, with scores 15.56 ± 6.01 versus 13.96 ± 4.67, respectively, when utilizing the community integration questionnaire, although our results did not reach the level of statistical significance [ 35 ]. Likewise, the frequency of marked/extreme global disability in females was lower than in males (36 vs 65%, respectively) when utilizing the Sheehan disability scale [ 34 ].…”
Section: Sex-specific Trends In Postinjury Sleep and Recovery After Worsupporting
confidence: 89%
“…They also experience difficulties in the psychosocial domain—often as a result of a combination of injury-related, psychological, and social factors [ 21 , 22 ], which predisposes them to a range of psychosocial and emotional problems [ 5 ]. Taken together, these consequences also hinder their reintegration into the community [ 23 ]. Fortunately, some of these consequences are at least amenable to rehabilitation.…”
Section: Introductionmentioning
confidence: 99%